(untitled) (Research, Society and Development, 2022)
Introduction: Obesity and Alzheimer’s Disease (AD) are chronic diseases that affect millions of people around the world. It is currently postulated that obesity may contribute to the establishment of AD. Objective: The aim of this study was to carry out a narrative literature review to analyze the effect of high-fat or high-sucrose obesogenic diets in an animal model and compare the establishment of behavioral changes and predictive AD biomarkers between these models. Method: Searches were performed in LILACS, SciELO and MEDLINE databases in the last ten years. The descriptors “obesity”, “Alzheimer’s disease” and “diets” were used. Results: Many studies employ high-fat obesogenic diets to assess the development of obesity and AD parameters. A much smaller number of studies employ obesogenic diets with high sucrose content, but both models show similarities in behavioral changes (memory and cognition deficit), in central biomarkers (beta-amyloid peptide and TAU protein), insulin resistance and neuroinflammation. Conclusion: It is noteworthy that studies with humans have pointed out neuroinflammation, resistance and accumulation of beta-amyloid peptide and hyperphosphorylated Tau protein as probable causes of neurodegeneration and consequent impairment of memory and cognition in AD.